2015
DOI: 10.1038/srep13849
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study for the inactivation of multidrug resistance bacteria using dielectric barrier discharge and nano-second pulsed plasma

Abstract: Bacteria can be inactivated through various physical and chemical means, and these have always been the focus of extensive research. To further improve the methodology for these ends, two types of plasma systems were investigated: nano-second pulsed plasma (NPP) as liquid discharge plasma and an Argon gas-feeding dielectric barrier discharge (Ar-DBD) as a form of surface plasma. To understand the sterilizing action of these two different plasma sources, we performed experiments with Staphylococcus aureus (S. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…First, we observed the OH radicals and found that after 4 min treatment in the Ar and Ar-O 2 plasma, the fluorescence intensity generated due to the reaction of terephthalic acid (TA) with OH (as described in our earlier work)31516, decreases with the addition of O 2 content. Similarly, for Ar-N 2 , the intensity decreases with the addition of N 2 content from 0.2% to 0.4%.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…First, we observed the OH radicals and found that after 4 min treatment in the Ar and Ar-O 2 plasma, the fluorescence intensity generated due to the reaction of terephthalic acid (TA) with OH (as described in our earlier work)31516, decreases with the addition of O 2 content. Similarly, for Ar-N 2 , the intensity decreases with the addition of N 2 content from 0.2% to 0.4%.…”
Section: Resultsmentioning
confidence: 72%
“…The H 2 O 2 was measured using titanyl ion, and NO was detected using 4-amino-5-methylamino-2′,7′-difluorofluo rescein (DAF-FM)36. OH was measured using terephthalic acid (20 mM), as per the procedure given in the earlier research work31136. NO 2 − was measured using the Griess reagent supplied by Aldrich Chemical Co. (USA)36.…”
Section: Experiments Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma medicine is a new field that uses NTP plasma for a diversity of medical applications 10 12 , such as sterilization 12 , wound healing 13 , blood coagulation 14 , 15 , and cancer treatment 16 . NTP plasma interacts with the oxygen, nitrogen, water, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial efficacy of NTP has been further confirmed by several groups (4,30,(38)(39)(40). NTP has been found to have antibacterial effects on a variety of bacteria (41,42), on ESKAPE pathogens in the environment (17), on multi-drugresistant bacteria in surface environments (43). Moreover, NTP has been shown to suppress host-cell invasion and to deactivate cell motility of Salmonella Typhimurium (44).…”
Section: High-touch and Frequently-touched Surfaces And Instruments Cmentioning
confidence: 88%